Sorafenib plus intensive chemotherapy improves survival in patients with newly diagnosed, FLT3‐internal tandem duplication mutation–positive acute myeloid leukemia. Issue 21 (16th July 2019) - Sasaki, Koji; Kantarjian, Hagop M.; Kadia, Tapan; Patel, Keyur; Loghavi, Sanam; Garcia‐Manero, Guillermo; Jabbour, Elias J.; DiNardo, Courtney; Pemmaraju, Naveen; Daver, Naval; Dalle, Iman Abou; Short, Nicholas; et al.
Abstract : Background: The addition of midostaurin to induction chemotherapy improves survival in younger patients with newly diagnosed, FLT3 –mutated acute myeloid leukemia (AML). Sorafenib is a potent multikinase inhibitor with efficacy when given as monotherapy. The authors investigated whether the addition of sorafenib to intensive induction chemotherapy improves outcomes in patients with FLT3 ‐internal tandem duplication (ITD)–mutated AML. Methods: In total, 183 patients who were newly diagnosed with FLT3 ‐ITD–mutated AML between February 2001 and December 2017 were identified. Of these, 79 patients (43%) underwent intensive chemotherapy with the addition of sorafenib, and 104 (57%) received intensive chemotherapy alone. Propensity score matching identified 42 patients in each cohort. Results: The overall response rate was 98% in the sorafenib cohort and 83% in the intensive chemotherapy cohort ( P = .057). The median follow‐up was 54 months. The median event‐free survival was 35 months in the sorafenib cohort and 8 months in the intensive chemotherapy cohort ( P = .019), and the median overall survival was 42 and 13 months, respectively ( P = .026). With censoring at the time of allogeneic stem cell transplantation, the median event‐free survival was 31 and 8 months in the sorafenib and intensive therapy cohorts, respectively ( P = .031), and the median overall survival was not reached and 10 months, respectively ( P = .001). Multivariate Cox proportional hazards models confirmed that treatment with sorafenib was a favorable prognostic factor ( P = .009; hazard ratio, 0.558; 95% CI, 0.360‐0.865). Conclusions: The addition of sorafenib improves survival in patients with FLT3 ‐ITD–mutated AML regardless of whether they undergo allogeneic stem cell transplantation. Abstract : The addition of sorafenib to intensive chemotherapy improves event‐free and overall survival durations in patients with FLT3‐internal tandem duplication–mutated acute myeloid leukemia. The survival benefit of sorafenib is independent of whether patients undergo allogeneic stem cell transplantation.